Caracterização e aplicação de sistemas micelares e microemulsionados como inibidores de corrosão - Roberto, Erileide Cavalcanti (2010)
Corrosion is an important phenomenon that frequently occurs in the oil industry, causing surface ablation, such as it happens on the internal surfaces of oil pipes. This work aims to obtain new systems to reduce this specific problem. The surfactants SDS, CTAB, and UNITOL L90 (in micellar and microemulsionated systems) were used as corrosion inhibitors. The systems were obtained using a C/S ratio of 2, butanol as cosorfactant, kerosene as oil phase and, as water phase, NaCl solutions of 0.5M with pH = 2, 4, and 7. Microemulsion regions were found both for direct and inverse micelles. SDS had the higher microemulsion region and the area was not dependent of pH. The study of micellization of these surfactans in the liquid-gas interface was carried out via the determination of CMC from surface tension measurements. Regarding microemulsionated systems, in the case of CTAB, CMC increased when pH was increased, being constant for SDS and UNITOL L90. Concerning micellar systems, increase in pH caused decrease and increase in CMC for SDC and CTAB, respectively. In the case of UNITOL L90, CMC was practically constant, but increased for pH = 4. The microemulsionated systems presented higher CMC values, except for UNITOL L90 L90. The negative values of free energy of micellization indicated that the process of adsorption was spontaneous. The results also indicated that, comparing microemulsionated to systems, adsorption was less spontaneous in the case of SDS and CTAB, while it did not change for UNITOL L90. SAXS experiments indicated that micelle geometry was spherical, existing also as halter and flat micelles, resuting in a better inght on the adsorption at the liquid-solid interface. Efficiency of corrosion inhibition as determined by electrochemical measurements, from corrosion currents calculated from Tafel extrapolation indicuting heat showed surfactants to be efficient even at low concentrations. Equilibrium isotherm data were fitted to the Freundlich model, indicating that surfactant adsorption occurs in the form of multilayers